Tactical and Forensic Features of The Search for Proceedings Involving the Forgery of Excise Stamps, Product Labels and Payment Cards - Ayupova, Zauresh; Mukanov, Malik; Begaliyev, Yernar (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of this article is to develop tactical features of an investigative action is a search for proceedings involving the forgery of excise stamps, product labels and payment cards. The analysis is reviewed on the list of grounds for conducting a search regulated by the Code of Criminal Procedure of the Republic of Kazakhstan, which makes the investigator limited in the ability to identify, seize traces in proceedings of the investigated category of proceedings. Based on these, the author has proposed recommendations for the provision of additional number of authorities for being searched premises.In this regard, a system of sequenced investigative examinations is being considered, accompanied by the examination of documents in the form of their preliminary study, and combined, if necessary, with the seizure of documents and objects by means of seizure and search. The recommendations are substantiated on the improvement of the organizational and tactical aspects of a search in the investigation of crimes related to the forgery of excise stamps, product labels and payment cards.